Synthesis, Crystal Structure, and Spectroscopic and Electronic Properties of N-[4-(3-Methyl-3-Phenyl-Cyclobutyl)-Thiazol-2-yl]-N?-Phenyl Hydrazine - Saracoglu, H.; Guntepe, F.; Yuksektepe, C.; Caliskan, N.; Cukurovali, A. (Taylor & Francis Ltd, 2011)
The title molecule, N-[4-(3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N '-phenyl hydrazine (C20H21N3S), was prepared and characterized by elemental analysis, H-1-NMR, C-13-NMR, FT-IR, UV-Visible (UV-Vis), and single-crystal X-ray diffraction. The compound crystallizes in the monoclinic space group P2(1)/c with a = 12.2960(5), b = 13.9565(5), c = 10.6356(5) angstrom, and beta = 99.106(3)degrees. Molecular geometries from X-ray experiment, vibrational frequencies, atomic charges distribution, dipole moments and total energies of the title compound and the dimer in the ground state have been calculated using the density functional theory method (RB3LYP) with 6-31G(d, p) and 6-311G(d, p) basis sets, and compared with the experimental data. Calculated results show that DFT at the RB3LYP/6-31G(d, p) and 6-311G(d, p) levels can well reproduce the structure of the title compound. To determine conformational flexibility, the molecular energy profile of the title compound was obtained by semi-empirical (RAM1) calculations with respect to the selected torsion angle, which was varied from -180 degrees to +180 degrees in steps of 10 degrees. In addition, the molecular electrostatic potential (MEP), frontier molecular orbitals, thermodynamic properties, and UV-Vis absorption spectra of the title compound were investigated using theoretical calculations. UV-Vis absorption spectra of the compound have been ascribed to their corresponding molecular structure and electrons orbital transitions.
Keywords: DFT calculations; hydrazine derivative; IR spectra; X-ray structure determination